2020
DOI: 10.3390/md18040178
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment of Nile Tilapia Skin (Oreochromis niloticus) Collagen Hydrogels for Wound Dressings

Abstract: Collagen plays an important role in the formation of extracellular matrix (ECM) and development/migration of cells and tissues. Here we report the preparation of collagen and collagen hydrogel from the skin of tilapia and an evaluation of their potential as a wound dressing for the treatment of refractory wounds. The acid-soluble collagen (ASC) and pepsin-soluble collagen (PSC) were extracted and characterized using sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE), differential scanning ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(101 citation statements)
references
References 71 publications
3
95
0
3
Order By: Relevance
“…These results demonstrated that aECM HCl,25 hydrogel was optimal with a sol form at 25 • C for easier application on the wound area and transforming into a gel form at 37 • C with a gel strength higher enough for firmly retaining. Pepsin-soluble collagen (PSC) hydrogel with similar rheological behaviors has been reported by Ge et al [15]. But it did not demonstrate that there exists a sol-gel transition characteristic at 37 • C for PSC hydrogel.…”
Section: Preparation and Characterization Of Aecm Hydrogelsmentioning
confidence: 77%
See 2 more Smart Citations
“…These results demonstrated that aECM HCl,25 hydrogel was optimal with a sol form at 25 • C for easier application on the wound area and transforming into a gel form at 37 • C with a gel strength higher enough for firmly retaining. Pepsin-soluble collagen (PSC) hydrogel with similar rheological behaviors has been reported by Ge et al [15]. But it did not demonstrate that there exists a sol-gel transition characteristic at 37 • C for PSC hydrogel.…”
Section: Preparation and Characterization Of Aecm Hydrogelsmentioning
confidence: 77%
“…The "wet wound healing theory" proposes that the wet healing environment is favorable to the granulation growth and to the enablement of the skin cell division, thereby promoting the complete wound healing [15]. Based on this theory, intrinsic characteristics of hydrogels or pastes are expectable to be advantageous for the wound healing process since they provide the dressing with desirable essential properties-better biocompatibility; protection from physical injury; optimal gaseous exchange and nutrients supply to cells due to high sponginess; additionally, their swellability allows for the absorption of excess exudates as well as the maintenance of an optimal moisture environment around the wound, which exhibited to accelerate the wound re-epithelialization process [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the collagen scaffold manufactured in this study could facilitate wound healing after transplantation onto wounds in the oral cavity. Applications of marine collagen as a biomimicking material, not only for hard tissues but also soft tissues including hemostats, has great potential in regenerative medicine 52,53 . www.nature.com/scientificreports/ In summary, our manufacturing system is valuable for fabricating a negative mold to replicate a variety of the biomimetic microstructures, such as DEJ on collagen scaffolds, implying competency of this technique to engineer scaffolds with a micropattern composed of a variety of hydrogels, such as the native topography of DEJ.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen from Oreochromis niloticus skin was used to prepare biomedical hydrogel. It has been proven that collagen hydrogel was able to heal of deep second-degree burn of rat skin [ 78 ]. Collagen accelerates wound healing by promoting the expression of vascular endothelial growth factor (VEGF), transforming growth factor-beta (TGF-ß1), basic fibroblast growth factor (bFGF), and alpha-smooth muscle actin (α-SMA) [ 79 ].…”
Section: Fish Byproducts As Source Of High Added-value Compoundsmentioning
confidence: 99%